"Everything Has Turned Against Us": Experiences of Left-Behind Spouses of Incarcerated Persons. Issue 48 (4th May 2022) - Yeboaa, Portia Akua; Mbamba, Crispin Rakibu; Ndemole, Ignatus Kpobi
Abstract: Incarceration comes with enormous role changes as left-behind spouses strive to adjust to daily living and survival. Consequently, this study explores the experiences of left-behind spouses as they strive to live their new lives without their partners, and to identify prevailing setbacks to draw practice implications. Evidence was collected through semi-structured qualitative interviews with 25 left-behind spouses of inmates in Nsawam Medium Security Prison, Ghana. Narratives were analyzed thematically following reflexive thematic analysis procedures. The study spotlights (1) psychological anxiety and trauma (2) social stigma and reduced socialization and (3) threatened marital divorce as predisposing challenges experienced by left-behind spouses of incarcerated persons. The study suggests the need for social service professionals like social workers, counselors, and psychiatrists to utilize Trauma-Focused Cognitive-Behavior Therapies (TF-CBT) to help left-behind spouses address distorted or upsetting attributions to help them cope with emotional distress and stressors. The study also recommends the need to explore informal social support from kin and kith of left behind spouses. The study proposes further research to solicit the views of left-behind spouses on the support systems available to them as they strive to cope with their new normal as this article focused only on identifying their challenges.